2005
DOI: 10.2224/sbp.2005.33.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Relationship Beliefs in Marital Satisfaction and Adjustment

Abstract: In this study we investigated the association between dysfunctional relationship beliefs and marital relationships of Turkish nonclinical married individuals. The Interpersonal Cognitive Distortions Scale (Hamamci & Büyüközturk, 2004), Dyadic Adjustment Scale (Spanier, 1976, and Marriage Life Scale (Tezer, 1986), which measure marital satisfaction, were administered to the sample of 190 married females and males. Analysis revealed that married individuals with low dyadic adjustment endorsed significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
25

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 43 publications
3
22
1
25
Order By: Relevance
“…The findings in the literature are consistent with our results (Yalçın, 2014;Hamamcı, 2005). Whereas, Aydınlı and Tutarel -Kışlak (2009) reported that individuals with a single child or without children had higher marital adjustment scores than those, who had three or more children.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The findings in the literature are consistent with our results (Yalçın, 2014;Hamamcı, 2005). Whereas, Aydınlı and Tutarel -Kışlak (2009) reported that individuals with a single child or without children had higher marital adjustment scores than those, who had three or more children.…”
Section: Discussionsupporting
confidence: 92%
“…Yalçın (2014) stated that women aged ≥ 41 years had high harmony with their husbands. However, other studies in the literature report no relation between marital adjustment and age group (Yeşiltepe and Çelik, 2014;Çınar, 2008;Hamamcı, 2005;Akbaş, 2008;Çetin, 2010). When these results are evaluated in consideration of the studies in the literature, it is believed that couples' empathy towards other and spending productive time together-rather than age groups-have a favorable and more significant effect on marital adjustment.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations